Anti-inflammatory activities of novel heat shock protein 90 isoform selective inhibitors in BV-2 microglial cells - Smith, Amanda G.; Kliebe, Valentin M.; Mishra, Sanket; McCall, Ryan P.; Irvine, Megan M.; Blagg, Brian S. J.; Lei, Wei (Frontiers in Molecular Biosciences, 2024)
Heat shock protein 90 (Hsp90) is a family of chaperone proteins that consists of four isoforms: Hsp90α, Hsp90β, glucose-regulated protein 94 (Grp94), and tumor necrosis factor type 1 receptor-associated protein (TRAP1). They are involved in modulating the folding, maturation, and activation of their client proteins to regulate numerous intracellular signaling pathways. Previous studies demonstrated that pan-Hsp90 inhibitors reduce inflammatory signaling pathways resulting in a reduction of inflammation and pain but show toxicities in cancer-related clinical trials. Further, the role of Hsp90 isoforms in inflammation remains poorly understood. This study aimed to determine anti-inflammatory activities of Hsp90 isoforms selective inhibitors on the lipopolysaccharide (LPS)-induced inflammation in BV-2 cells, a murine microglial cell line. The production of inflammatory mediators such as nitric oxide (NO), interleukin 1 beta (IL-1β), and tumor necrosis factor-alpha (TNF-α) was measured. We also investigated the impact of Hsp90 isoform inhibitors on the activation of nuclear factor kappa B (NF-κB), nuclear factor erythroid 2–related factor 2 (Nrf2), and mitogen-activated protein kinases (MAPKs). We found that selective inhibitors of Hsp90β reduced the LPS-induced production of NO, IL-1β, and TNF-α via diminishing the activation of NF-κB and Extracellular signal-regulated kinases (ERK) MAPK. The Hsp90α, Grp94, TRAP1 inhibitors had limited effect on the production of inflammatory mediators. These findings suggest that Hsp90β is the key player in LPS-induced neuroinflammation. Thereby providing a more selective drug target for development of medications involved in pain management that can potentially contribute to the reduction of adverse side effects associated with Hsp90 pan inhibitors.